(untitled) (Al-Academy, 2018)
The research aims at benefiting from the technological development and the technical progress. This development necessitated that the educational process take advantage of this progress, and the development of special computer software, especially the design programs, made the two researchers think about how to benefit from these design programs in teaching students the skills of theatrical design. The current search aims at: Identifying the effect of 3Ds Max in developing the skill of theatrical decoration design among the students of the Department of Art Education "Third stage / Department of Art Education / Faculty of Fine Arts / University of Diyala for the academic year 2014-2015. The researchers used the experimental method of the two groups (controlling and experimental) and pretest and posttest method to achieve the objective of the research. The sample was selected from the students of the third stage / Department of Art Education for the academic year 2014/2015. The sample was randomized into two groups: the experimental group consisted of (15) students who studied through the use of 3Ds Max and the controlling group consisted of (15) students who studied in the traditional way. The researchers prepared a form for evaluating the skill performance of the theatrical decoration design. This form consisted of (10) paragraphs with a five-point scale and a percentage weight of five degrees. After preparing the research tool and achieving its validity and stability, the research was applied for eight weeks. The data attained were statistically processed and the results were reached at and the most notably effective of which was the 3Ds Max program in the development of the skill of the theatrical decoration design among students of the Department of Art Education.